Role of 18F-FDG positron emission tomography in carotid atherosclerotic plaque imaging: A systematic review - Ravikanth, Reddy (World Journal of Nuclear Medicine, 2020)
Stroke and other thromboembolic events in the brain are often due to carotid artery atherosclerosis, and atherosclerotic plaques with inflammation are considered particularly vulnerable, with an increased risk of becoming symptomatic. Positron emission tomography (PET) with 2-deoxy-2-[Fluorine-18] fluoro-D-glucose (18F-FDG) provides valuable metabolic information regarding arteriosclerotic lesions and may be applied for the detection of vulnerable plaque. At present, however, patients are selected for carotid surgical intervention on the basis of the degree of stenosis alone, and not the vulnerability or inflammation of the lesion. During the past decade, research using PET with the glucose analog tracer 18F-fluor-deoxy-glucose, has been implemented for identifying increased tracer uptake in symptomatic carotid plaques, and tracer uptake has been shown to correlate with plaque inflammation and vulnerability. These findings imply that 18F-FDG PET might hold the promise for a new and better diagnostic test to identify patients eligible for carotid endarterectomy. The rationale for developing diagnostic tests based on molecular imaging with 18F-FDG PET, as well as methods for simple clinical PET approaches, are discussed. This is a systematic review, following Preferred Reporting Items for Systematic Reviews guidelines, which interrogated the PUBMED database from January 2001 to November 2019. The search combined the terms, “atherosclerosis,” “inflammation,” “FDG,” and “plaque imaging.” The search criteria included all types of studies, with a primary outcome of the degree of arterial vascular inflammation determined by 18F-FDG uptake. This review examines the role of 18F-FDG PET imaging in the characterization of atherosclerotic plaques.
Keywords: 18F-FDG; atherosclerosis; carotid artery; carotid endarterectomy; plaque imaging; vulnerable plaque